Ethyl 3-methyl-5-nitro-1H-imidazole-2-carboxylate - Wu, H.Q.; Ng, S.W.; Zain, Sharifuddin Md; Gu, L.Q.; Huang, Z.S.; An, L.K. (International Union of Crystallography, 2004)
The structure determination of the compound C7H 9N3O4 reagent that is used in the synthesis of a class of pyschoactive drugs was investigated. It was found that the molecule of the compound was flat in the imidazole portion, but the carboxethyl group was twisted by 15.0 (1)° The compound was synthesized using a published procedure and crystals were obtained by recrystallization from diethyl ether. The structure from the x ray measurements was used for the calculation of the potential energy surface at the PM3 level using HyperChem.